Extracapsular dissection (ECD) and extended ECD: description of the technique and outcome of treatment. Issue 8 (October 2022) - Chegini, Soudeh; Sassoon, Isabel; McGurk, Mark
Abstract: Over the last two decades the senior author has exclusively applied the technique of extracapsular dissection (ECD) and extended ECD to treat discrete, apparently benign parotid tumours. This article describes both techniques and evaluates their application. Simple principles are described to anticipate unexpected malignant tumours and manage lumps safely by wide excision. A retrospective analysis of 97 consecutive patients with discrete, apparently benign parotid lumps is presented. The tumours were classified using the European Salivary Gland Society (ESGS) classification for benign tumours of the parotid gland. The ECD or extended ECD technique was employed irrespective of tumour site or size. A review of patients was carried out after a minimum of six months post surgery by two independent clinicians. The mean (range) hospital stay was one (0-4) night (median 1). Complications were both modest and transient. The temporary facial nerve injury rate was 5/97 (6%). Other complications included haematoma (n=2), sialocele (n=2), and first-bite syndrome (n=2). Independent review post surgery demonstrated a mean Sunnybrook facial grading system score of 98/100 and a mean Stony Brook scar assessment score of 4.5/5. In this series 5/97 (5%) of discreet mobile lumps concealed a low-grade salivary cancer. Experience with the application of ECD in conjunction with its extended form in 97 consecutive patients with discrete parotid lumps is described. The technique is amenable to all parotid lumps, is not restricted by site or size, and has shown minimal morbidity. The risk of recurrent disease could not be addressed.